PERSPEKTIF KEWENANGAN KEJAKSAAN ATAS PELAKSANAAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA RINGAN DI KEJAKSAAN NEGERI OGAN ILIR - Iqram Syah Putra (2022)
The Prosecutor's Office of the Republic of Indonesia is one of the law enforcement agencies and state institutions whose function is to exercise state power, especially in the field of prosecution. The problems raised in this thesis are how the arrangements related to the prosecutor's authority for the implementation of restorative justice and how to implement the application of restorative justice in the settlement of minor crimes at the Ogan Ilir District Prosecutor's Office. Restorative justice is considered capable of being a solution in resolving cases quickly with the main principle of prioritizing participation between victims, perpetrators and the community. The implementation of the application of Restorative justice as a model for resolving cases at this time can be used as a guide in cases of minor crimes as regulated in the Indonesian Prosecutor's Office Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative justice, especially the implementation carried out by the Ogan Ilir District Prosecutor's Office. This research was carried out with a statute approach using library data, namely normative juridical which was carried out by examining library materials or secondary materials that were collected and analyzed and researched. The authority of the Prosecutor's Office in the implementation of Restorative Justice is expressly regulated in the Indonesian Prosecutor's Office Regulation Number 15 of 2020 concerning Termination of Prosecution based on Restorative Justice and Implementation of Restorative Justice at the Ogan Ilir District Prosecutor's Office since the issuance of the Regulation is still quite low, which is because there are still several obstacles, both internal and external in its implementation. Keywords: prosecutor, restorative justice, minor crimes